Calvino-Desai, On Freedom and Alienation : Rules and Boundaries of Life on a Tree - Radoš-Perković, Katja (2012)
Both Italo Calvino (The Baron in the Trees) and, much later, Kiran Desai (Hullabaloo in the Guava Orchard) created an alternative life-space above ground, on the trees. In case of Calvino's character Cosimo, it is a life-long experience, we follow Cosimo from childhood to maturity in the new environment as he takes an active part in the important historical events of his new surroundings. Desai's Sampath ends up on a guava tree almost by accident, in his adult age, and does not control the repercussions of this choice. The paper discusses the similarities and differences between the two different concepts of freedom advocated by the characters, along with the inevitable rules and boundaries attached to these utopias.
ENG